Inducing disorder in order: hierarchically porous covalent organic framework nanostructures for rapid removal of persistent organic pollutants - Karak, Suvendu; Dey, Kaushik; Torris, Arun; Halder, Arjun; Bera, Saibal; Kanheerampockil, Fayis; Banerjee, Rahul (Journal of the American Chemical Society, 2019)
The key factor responsible for fast diffusion and mass transfer through a porous material is the availability of a widely open pore interior having complete accessibility from their surface. However, because of their highly stacked nature, ordered two-dimensional (2D) materials fail to find real-world applicability, as it is difficult to take advantage of their complete structure, especially the inner cores. In this regard, three-dimensional (3D) nanostructures constructed from layered two-dimensional crystallites could prove to be advantageous. However, the real challenge is to cultivate a porous nanostructure with ordered pores where the pores are surrounded by crystalline walls. Herein, a simple yet versatile in situ gas-phase foaming technique has been employed to address these cardinal issues. The use of baking soda leads to the continuous effervescence of CO2 during the crystallization of foam, which creates ripples and fluctuations on the surface of the 2D crystallites. The induction of ordered micropores within the disordered 3D architecture synergistically renders fast diffusion of various guests through the interconnected pore network. The high-density defects in the hierarchically porous structure help in ultrafast adsorption (<10 s) of various pollutants (removal efficiency of 99%) from water, all of which would lead to significant environmental benefit. The pseudo-second-order rate constant for the BPA pollutant is 182.3 g mg(-1) min(-1), which is the highest among all the literature reports to date. The high removal efficiency (highest efficiency of 94% and average efficiency of 70%) of a persistent organic pollutant has been attended for the first time.

Role of particle morphology in the yielding behavior of dense thermosensitive microgel suspensions - Jathavedan, Kiran Kaithakkal; Kanheerampockil, Fayis; Bhat, Suresh (Journal of Applied Polymer Science, 2019)
The yielding behavior of dense thermosensitive microgel suspensions of poly(N-isopropylacrylamide) with two different particle morphologies viz core-shell (CS) morphology and particles with uniform crosslink density were studied. Structural properties were examined using dynamic light scattering and yielding behavior was investigated by nonlinear oscillatory rheology. Suspensions of particles with uniform crosslinking density showed a typical hard sphere like behavior with the loss modulus (G `') exhibiting a single peak due to cage breaking while CS type particles shows a double yielding at different ranges of strain similar to that seen in attractive colloidal glasses. The first yielding process in CS microgels is interpreted as due to the disentanglement of the overlapped polymer chains from the shells of the neighboring microgels and the second yielding process due to the breakage of cages formed by neighboring microgel particles. Current study suggests that the interpenetration of polymer chains at high concentrations sets in an attractive like potential leading to double yielding phenomena in an otherwise purely repulsive system. (c) 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2019, 137, 48625.

Connecting microscopic structures, mesoscale assemblies, and macroscopic architectures in 3D-printed hierarchical porous covalent organic framework foams - Mohammed, Abdul Khayum; Usgaonkar, Saurabh; Kanheerampockil, Fayis; Karak, Suvendu; Halder, Arjun; Tharkar, Minakshi; Addicoat, Matthew; Ajithkumar, Thalasseril G.; Banerjee, Rahul (Journal of the American Chemical Society, 2020)
The induction of macro and mesopores into two-dimensional porous covalent organic frameworks (COFs) could enhance the exposure of the intrinsic micropores toward the pollutant environment, thereby, improving the performance. However, the challenge is to build a continuous hierarchically porous macro-architecture of crystalline organic materials in the bulk scale. In this regard, we have strategized a novel synthetic method to create hierarchically porous COF foams consisting of ordered micropores (2-2.2 nm) and disordered meso and macropores (50 nm to 200 mu m) as well as ordered macropores (1.5 mm to 2 cm). Herein, graphene oxide was used for creating disordered macro and mesopores in COF-GO foams. Considering the rheological features of the precursor hydrogel, we could integrate crystalline and porous COF-GO foams into self-supported three-dimensional (3D)-printed objects with the desired shapes and sizes. Therefore, we have engineered the 3D macro-architecture of COF-GO foams into complex geometries keeping their structural order and continuous porosity intact over a range of more than a million (10(-9) m to 10(-3) m). The interconnected 3D openings in these COF-GO foams further enhance the rapid and efficient uptake of organic and inorganic pollutants from water (>95% removal within 30 s). The abundant distribution of interconnected macroporous volume (55%) throughout the COF-GO foam matrix enhances the flow of water (1.13 x 10(-3) m.s(-1)) which results in efficient mass transport and adsorption.

Hierarchical nanoflower arrays of Co9S8-Ni3S2 on nickel foam: a highly efficient binder-free electrocatalyst for overall water splitting - Illathvalappil, Rajith; Walko, Priyanka S.; Kanheerampockil, Fayis; Bhat, Suresh K.; Devi, R. Nandini; Kurungot, Sreekumar (Chemistry-A European Journal, 2020)
Hydrogen production is vital for meeting future energy demands and managing environmental sustainability. Electrolysis of water is considered as the suitable method for H-2 generation in a carbon-free pathway. Herein, the synthesis of highly efficient Co9S8-Ni3S2 based hierarchical nanoflower arrays on nickel foam (NF) is explored through the one-pot hydrothermal method (Co9S8-Ni3S2/NF) for overall water splitting applications. The nanoflower arrays are self-supported on the NF without any binder, possessing the required porosity and structural characteristics. The obtained Co9S8-Ni3S2/NF displays high hydrogen evolution reaction (HER), as well as oxygen evolution reaction (OER), activities in 1 m KOH solution. The overpotentials exhibited by this system at 25 mA cm(-2) are nearly 277 and 102 mV for HER and OER, respectively, in 1 m KOH solution. Subsequently, the overall water splitting was performed in 1 m KOH solution by employing Co9S8-Ni3S2/NF as both the anode and cathode, where the system required only 1.49, 1.60, and 1.69 V to deliver the current densities of 10, 25, and 50 mA cm(-2), respectively. Comparison of the activity of Co9S8-Ni3S2/NF with the state-of-the-art Pt/C and RuO2 coated on NF displays an enhanced performance for Co9S8-Ni3S2/NF both in the half-cell as well as in the full cell, emphasizing the significance of the present work. The post analysis of the material after water electrolysis confirms that the surface Co(OH)(2) formed during the course of the reaction serves as the favorable active sites. Overall, the activity modulation achieved in the present case is attributed to the presence of the open-pore morphology of the as formed nanoflowers of Co9S8-Ni3S2 on NF and the simultaneous presence of the surface Co(OH)(2) along with the highly conducting Co9S8-Ni3S2 core, which facilitates the adsorption of the reactants and subsequently its conversion into the gaseous products during water electrolysis.
Keywords: cobalt sulfide; electrocatalysts; Hydrogen evolution; overall water splitting; oxygen evolution

Active site engineering and theoretical aspects of ``Superhydrophilic'' nanostructure array enabling efficient overall water electrolysis - Barik, Sidharth; Kharabe, Geeta Pandurang; Illathvalappil, Rajith; Singh, Chandrodai Pratap; Kanheerampockil, Fayis; Walko, Priyanka S.; Bhat, Suresh K.; Devi, R. Nandini; Vinod, C. P.; Krishnamurty, Sailaja; Kurungot, Sreekumar (Small, 2023)
The rational design of noble metal-free electrocatalysts holds great promise for cost-effective green hydrogen generation through water electrolysis. In this context, here, the development of a superhydrophilic bifunctional electrocatalyst that facilitates both oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) in alkaline conditions is demonstrated. This is achieved through the in situ growth of hierarchical NiMoO4@CoMoO4 center dot xH(2)O nanostructure on nickel foam (NF) via a two-step hydrothermal synthesis method. NiMoO4@CoMoO4 center dot xH(2)O/NF facilitates OER and HER at the overpotentials of 180 and 220 mV, respectively, at the current density of 10 mA cm(-2). The NiMoO4@CoMoO4 center dot xH(2)O/NF parallel to NiMoO4@CoMoO4 center dot xH(2)O/NF cell can be operated at a potential of 1.60 V compared to 1.63 V displayed by the system based on the Pt/C@NF parallel to RuO2@NF standard electrode pair configuration at 10 mA cm(-2) for overall water splitting. The density functional theory calculations for the OER process elucidate that the lowest Delta G of NiMoO4@CoMoO4 compared to both Ni and NiMoO4 is due to the presence of Co in the OER catalytic site and its synergistic interaction with NiMoO4. The preparative strategy and mechanistic understanding make the windows open for the large-scale production of the robust and less expensive electrode material for the overall water electrolysis.
Keywords: density functional theory (DFT) study; hydrogen evolution reaction (HER); Hydrothermal synthesis; oxygen evolution reaction (OER); superhydrophilic nanostructures; synergistic interaction; water electrolysis

Cobalt-manganese modified theophrastite phase of nickel hydroxide nanoflower arrays on nickel foam as a self-standing bifunctional electrode for overall water electrolysis - Kharabe, Geeta Pandurang; Illathvalappil, Rajith; Barik, Sidharth; Kanheerampockil, Fayis; Walko, Priyanka S.; Bhat, Suresh K.; Devi, R. Nandini; Kurungot, Sreekumar (Sustainable Energy & Fuels, 2023)
Designing and developing self-supported electrodes for water electrolysis is attractive as compared to conventional catalyst-coated electrodes. Herein, a (Co0.3Mn0.1Ni0.6)(OH)(2)/NF nanocomposite is prepared by anchoring (Co0.3Mn0.1Ni0.6)(OH)(2)via simple one-pot hydrothermal synthesis on nickel foam. The presence of Mn induces the external electronic structure of Co(OH)(2), and this also improves the electrochemically active surface area (ECSA). These favor better accessibility of active sites and increased intrinsic activity for the OER and HER. (Co0.3Mn0.1Ni0.6)(OH)(2)/NF has shown promising electrochemical activity toward the OER and HER in a 1 M KOH electrolyte, with an overpotential of 270 mV for the OER and 163 mV for the HER to deliver 10 mA cm(-2) current density. The overall water splitting was performed by employing (Co0.3Mn0.1Ni0.6)(OH)(2)/NF as both the cathode and anode by displaying a voltage of 1.62 V at 10 mA cm(-2), which is comparable to that extracted from a similar system based on the state-of-the-art Pt/C@NF cathode and RuO2@NF anode (1.60 V at 10 mA cm(-2)) standard electrode pair. Interestingly, at high current densities, the (Co0.3Mn0.1Ni0.6)(OH)(2)/NF//(Co0.3Mn0.1Ni0.6)(OH)(2)/NF system displayed better overall water splitting performance (1.78 V at 100 mA cm(-2)) compared to its Pt/C@NF//RuO2@NF (1.89 V at 100 mA cm(-2)) counterpart while displaying a stable output during the evolution period that lasted for 24 h. The amounts of H-2 and O-2 produced are estimated to be 701.2 and 358.6 mmol, respectively, at a time interval of 1 h; these amounts correspond to an similar to 1 : 2 ratio of O-2 and H-2, respectively. This study confirms the capability for employing (Co0.3Mn0.1Ni0.6)(OH)(2)/NF as a bi-functional and self-standing electrode for the realistic demonstrations of overall water splitting applications.

Electrode|electrolyte interface enhancement in quasi-solid-state zinc-air batteries through an anion conducting polymer electrolyte interlayer by in situ polymerization - Kurian, Maria; Vijayakumar, Vidyanand; Manna, Narugopal; Kanheerampockil, Fayis; Bhat, Suresh; Kurungot, Sreekumar (Journal of Materials Chemistry A, 2023)
This work introduces a novel concept of electrode|electrolyte interface enhancement using an ultraviolet (UV) light-assisted in situ polymerization strategy to improve the performance of quasi-solid-state zinc-air batteries (ZABs). The suitability of the UV polymerization strategy to process a mechanically stable OH- conducting anion exchange polymer electrolyte membrane (AEPEM) reinforced by a glass fiber (GF) separator is also reported. The in situ polymerized ionomer-skin/interlayer (a thin anion-conducting polymer coating over the air-cathode of ZAB) acts as a buffer layer to narrow down the performance gap generally observed between ZABs possessing quasi-solid-state electrolytes and standard liquid electrolytes, respectively. For instance, when combined with the in situ polymerization strategy, a rechargeable ZAB (rZAB) based on an AEPEM-GF composite membrane delivered a high power density of 140 mW cm(-2), higher than that of the one without an in situ polymerized ionomer interlayer (120 mW cm(-2)). Notably, in a flexible rZAB configuration, this new strategy resulted in enhanced rate capability and cycling stability for 14 h at an operating current density of 2 mA cm(-2).

Cathode|electrolyte interface engineering by a hydrogel polymer electrolyte for a 3D porous high-voltage cathode material in a quasi-solid-state zinc metal battery by in situ polymerization - Puthiyaveetil, Priyanka Pandinhare; Torris, Arun; Dilwale, Swati; Kanheerampockil, Fayis; Kurungot, Sreekumar (SMALL, 2024)
This work highlights the development of a superior cathode|electrolyte interface for the quasi solid-state rechargeable zinc metal battery (QSS-RZMB) by a novel hydrogel polymer electrolyte using an ultraviolet (UV) light-assisted in situ polymerization strategy. By integrating the cathode with a thin layer of the hydrogel polymer electrolyte, this technique produces an integrated interface that ensures quick Zn2+ ion conduction. The coexistence of nanowires for direct electron routes and the enhanced electrolyte ion infiltration and diffusion by the 3D porous flower structure with a wide open surface of the Zn-MnO electrode complements the interface formation during the in situ polymerization process. The QSS-RZMB configured with an integrated cathode (i-Zn-MnO) and the hydrogel polymer electrolyte (PHPZ-30) as the separator yields a comparable specific energy density of 214.14 Wh kg(-1) with that of its liquid counterpart (240.38 Wh kg(-1), 0.5 M Zn(CF3SO3)(2) aqueous electrolyte). Other noteworthy features of the presented QSS-RZMB system include its superior cycle life of over 1000 charge-discharge cycles and 85% capacity retention with 99% coulombic efficiency at the current density of 1.0 A g(-1), compared to only 60% capacity retention over 500 charge-discharge cycles displayed by the liquid-state system under the same operating conditions.
Keywords: cathode-electrolyte interface tuning; dendrite inhibition; epitaxial zinc deposition; hydrogel polymer electrolyte; In situ polymerization; Quasi solidstate rechargeable zinc metal battery

Ultralight crystalline hybrid composite material for highly efficient sequestration of radioiodine - Fajal, Sahel; Mandal, Writakshi; Torris, Arun; Majumder, Dipanjan; Let, Sumanta; Sen, Arunabha; Kanheerampockil, Fayis; Shirolkar, Mandar M.; Ghosh, Sujit K. (Nature Communications, 2024)
Considering the importance of sustainable nuclear energy, effective management of radioactive nuclear waste, such as sequestration of radioiodine has inflicted a significant research attention in recent years. Despite the fact that materials have been reported for the adsorption of iodine, development of effective adsorbent with significantly improved segregation properties for widespread practical applications still remain exceedingly difficult due to lack of proper design strategies. Herein, utilizing unique hybridization synthetic strategy, a composite crystalline aerogel material has been fabricated by covalent stepping of an amino-functionalized stable cationic discrete metal-organic polyhedra with dual-pore containing imine-functionalized covalent organic framework. The ultralight hybrid composite exhibits large surface area with hierarchical macro-micro porosity and multifunctional binding sites, which collectively interact with iodine. The developed nano-adsorbent demonstrate ultrahigh vapor and aqueous-phase iodine adsorption capacities of 9.98 g.g-1 and 4.74 g.g-1, respectively, in static conditions with fast adsorption kinetics, high retention efficiency, reusability and recovery. The development of effective adsorbents of radioiodine nuclear waste remains difficult due to the lack of proper material design strategies. Here the authors report an ultralight hierarchically porous crystalline multifunctional hybrid nanocomposite for ultrafast entrapment of iodine and polyiodide species under both static and dynamic condition.

Anode|electrolyte|cathode interface engineering to develop a robust zinc metal hydrogel battery - Dilwale, Swati; Babu, Athira; Kanheerampockil, Fayis; Torris, Arun; Puthiyaveetil, Priyanka Pandinhare; Bhat, Suresh; Kurungot, Sreekumar (Journal of Materials Chemistry A, 2025)
The poor electrode-electrolyte interfaces in quasi-solid-state zinc metal batteries often hinder Zn2+ ion transport due to the poor compatibility of the gel electrolyte with the electrodes. This report proposes a dual-interface engineering strategy across the anode, cathode, and separator using a single hydrogel polymer electrolyte (HPE). The integration of vanadyl phosphate functionalized carbon nanotubes (VP/fCNT) into a commercial glass fiber (GF) separator, followed by a thin hydrogel coating and UV-light photopolymerization, resulted in a dual-interface engineered cathode-separator-electrolyte structure (VP/IC-EGF). To mitigate the dendritic growth, an artificial solid electrolyte interface was developed on Zn foil (AEI@Zn). The engineered GF (EGF) demonstrates a room-temperature conductivity of 6.5 mS cm-1 and a high electrochemical stability window of 2.4 V vs. Zn|Zn2+. The symmetric cell with AEI@Zn|EGF|AEI@Zn exhibits exceptional plating/stripping stability over 1400 h at a current density of 0.1 mA cm-2 and a capacity of 0.1 mAh cm-2. Moreover, the low-volume cell (AEI@Zn & Vert;VP/IC-EGF), featuring the dual-interface-engineered cathode-separator-electrolyte, demonstrates outstanding cycling stability with over 3000 charge-discharge cycles at a current rate of 1.0 A g-1, retaining 98-99% of its initial capacity and showing high coulombic efficiency. These findings underscore the significant impact of interface engineering on enhancing the performance of ZMBs.